The Influence of Sharia Financial Literacy and Religious Attitudes on Investment Behavior among Muslim Millennials in Indonesia - Wilistiningsih, Sri; Pahrijal, Rival; Nurhasanah, Dila Padila (West Science Islamic Studies, 2025)
This study investigates the influence of Sharia financial literacy and religious attitudes on investment behavior among Muslim millennials in Indonesia. The research aims to understand how financial knowledge grounded in Islamic principles and religious commitment shape investment decision-making in a faith-based context. Using a quantitative research design, data were collected from 175 respondents through a structured questionnaire employing a Likert scale (1–5). The data were analyzed using SPSS version 25, including validity, reliability, and multiple regression tests. The findings reveal that both Sharia financial literacy and religious attitudes have positive and significant effects on investment behavior. The regression model shows that Sharia financial literacy contributes more strongly, indicating that higher understanding of Islamic financial concepts enhances rational and ethical investment choices. The coefficient of determination (R² = 0.537) demonstrates that both variables explain 53.7% of the variation in investment behavior. The study concludes that a combination of financial competence and religious values fosters responsible, Sharia-compliant investment behavior among young Muslim investors. These findings suggest that promoting Islamic financial education and strengthening religious awareness can enhance sustainable participation in the Islamic financial market.